Differences in the closeness of spatial relationship between Ricanidae in their prime and natural enemies in five kinds of tea gardens. Issue 8 (17th August 2022) - Cheng, Xian; Zhang, Lin; Wu, Xiaomeng; Xu, Yue; Sun, Jiazhao; Zhou, Xiazhi; Zou, Yunding; Bi, Shoudong
Abstract: To identify the natural enemy species which are close to Ricanidae in spatial relationship and to provide scientific basis for biological control and reasonable protection of natural enemies, geostatistics and the angular cosine coefficient method were used to analyze the population of Ricanidae in their prime and their natural enemies in the Anji white tea garden, the Longjing43 tea garden, the Nongkangzao tea garden, the Pingyangtezao tea garden and the Wuniuzao tea garden. The spatial relationship between six natural enemies and Ricanidae was also studied. The angular cosine coefficients were normalized to obtain the intimacy index. According to the sum of the intimacy index and the serial number of the intimacy index of each natural enemy in five tea gardens, the following conclusions could be drawn: the top three natural enemies closely related to Ricanidae in spatial relationship were Clubiona reichlini, Clubiona japonicola and Misumenops tricuspidatus ; at least two species of the top three natural enemies in each tea garden were the same as the top three natural enemies in the comprehensive analysis of the five tea gardens; one of the factors that determined the spatial relationship between natural enemies and Ricanidae was the ratio of the number of Ricanidae and natural enemies. The results of this study identified the spider species of natural enemies which should be rationally used and protected in the five tea gardens.